2019
DOI: 10.1371/journal.pone.0224219
|View full text |Cite
|
Sign up to set email alerts
|

Relations between gross motor skills and executive functions, controlling for the role of information processing and lapses of attention in 8-10 year old children

Abstract: This study aimed to systematically investigate the relation between gross motor skills and aspects of executive functioning (i.e. verbal working memory, visuospatial working memory, response inhibition and interference control) in 8–10 year old children. Additionally, the role of information processing (speed and variability) and lapses of attention in the relation between gross motor skills and executive functions was investigated. Data of 732 Dutch children from grade 3 and 4 were analyzed (50.0% boys, 50.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 75 publications
2
34
1
1
Order By: Relevance
“…Interestingly, previous research has indicated that while interrelations between cognitive and motor functions found in young adults appear rather specific (but less strong), the connection between the two domains seems to be stronger at the extreme ends of the lifespan (Livesey et al, 2006;Stöckel and Hughes, 2016;Oberer et al, 2017;Spedden et al, 2017;Stöckel et al, 2017;van der Fels et al, 2019). As such, a first aim of the present study was to assess if, and how, the cognitivemotor functions of preschoolers differ from that of young adults, who served as a control group representing the upper bound of cognitive-motor development.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous research has indicated that while interrelations between cognitive and motor functions found in young adults appear rather specific (but less strong), the connection between the two domains seems to be stronger at the extreme ends of the lifespan (Livesey et al, 2006;Stöckel and Hughes, 2016;Oberer et al, 2017;Spedden et al, 2017;Stöckel et al, 2017;van der Fels et al, 2019). As such, a first aim of the present study was to assess if, and how, the cognitivemotor functions of preschoolers differ from that of young adults, who served as a control group representing the upper bound of cognitive-motor development.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies have shown that gross motor skills are related to the executive functions that are most directly involved in gross motor tasks in children, such as visuospatial working memory (VSWM) (Rigoli, Piek, Kane, & Oosterlaan, 2012;van der Fels et al, 2019). VSWM refers to the ability to maintain and manipulate visuospatial information over brief periods of time (Baddeley & Hitch, 1994).…”
Section: Gross Motor Skills and Visuospatial Working Memorymentioning
confidence: 99%
“…Therefore, we could have missed aspects of gross motor skills that might have been related to VSWM-related brain activity. Furthermore, the review by van der Fels et al (2015) showed that the strongest relationships are found between complex motor skills (e.g., fine motor skills or bilateral body coordination) and executive functions. Circuit-based assessments have recently emerged as a dynamic method and more complex way of measuring motor skills.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations